Research on distributed beamforming synchronization technology in inter-satellite link system - Jianyun Chen; Zhang Yonggang; Sili Liu (Measurement + Control, 2022)
Limited by satellite load and carrying capacity, it is difficult for inter-satellite link systems to improve information transmission capabilities by increasing power and antenna size like traditional terrestrial communication systems. Satellite communication payload power has always been an important limitation of long-distance communication performance. In order to improve the satellite’s long-distance communication capability and comprehensively consider the characteristics of Doppler frequency changes in the satellite environment, we propose a cooperative communication algorithm based on weak bit feedback. This algorithm can realize the time and space focusing of the beams emitted by multiple distributed satellite nodes at the destination node, and improve the performance of satellite long-distance communication. This paper simulates the above algorithm based on STK/Matlab software. The simulation results show that the weak bit feedback algorithm has stronger adaptability, faster convergence speed and higher synthesis efficiency under different channel changes. The algorithm is simple and easy to implement, and is suitable for the inter-satellite link environment with many satellite nodes and high scalability. Finally, we conducted hardware experimental verification, analyzed the signal flow of each module in the hardware, and tested it on the USRP software radio platform. The test results show that it is a feasible solution to realize distributed satellite node cooperative communication based on the weak bit feedback algorithm.